Visual Screening of Chloride (Cl?) Ions Using a Colorimetric Sensor with Comparative Anion Study - Ahmad Fudhail Majid; A. Irma Suryani (PT ARRUS Intelektual Indonesia, 2025)
The presence of inorganic anions, particularly chloride (Cl?), nitrate (NO??), and sulfate (SO?²?), in aquatic environments and food products necessitates effective monitoring. Excessive concentrations of these anions may compromise fishery product quality and pose risks to human health. This study presents a visual screening approach for Cl? ions that leverages comparative colorimetric responses of NO?? and SO?²? ions. The method employs a colorimetric indicator that generates distinct color changes upon interaction with target anions, allowing distinct visual differentiation between Cl- ions and competing anions. Experimental results demonstrate a marked and concentration-dependent color change toward Cl? ions in the 10–100 µM range, whereas NO?? and SO?²? elicit only weak or negligible visual responses, even at higher concentrations. The strong contrast in visual response underscores the selectivity of this screening strategy toward Cl- ions. These findings suggest that the approach has potential as a rapid, practical, and cost-effective method for preliminary screening of inorganic anions in environmental and food monitoring applications.